P025 Lung cancer risk among firefighters when accounting for tobacco smoking – preliminary results from a pooled analysis of case-control studies from europe, canada, new zealand and china. (1st September 2016) - Bigert, Carolina; Gustavsson, Per; Straif, Kurt; Taeger, Dirk; Pesch, Beate; Kendzia, Benjamin; Schüz, Joachim; Stücker, Isabelle; Guida, Florence; Brüske, Irene; Wichmann, Heinz-Erich; Pesatori, Angela C; et al.
Abstract : Objectives: Firefighters are potentially exposed to a wide variety of chemical compounds during the course of their work and inhalation is considered to be the major source of exposure. A large number of human carcinogens have been detected in smoke at fires. The aim was to investigate the risk of lung cancer among firefighters, while controlling for smoking habits. Methods: We used data from the SYNERGY project including pooled information on lifetime work histories and smoking habits for 14, 748 male lung cancer cases and 17, 543 controls from 14 case-control studies conducted in Europe, Canada, New Zealand and China. There were 190 men who had ever worked as a firefighter (based on ISCO-68), among them 86 cases and 104 controls. Odds ratios (OR) and 95% confidence intervals (CI) were estimated by unconditional logistic regression, adjusted for study, age, smoking, and ever employment in an occupation with established lung cancer risk. Results: We observed no increased risk of lung cancer in firefighters, neither before (OR = 1.03, 95% CI: 0.77–1.38) nor after (OR = 0.95, 95% CI: 0.68–1.32) adjustment for smoking and exposure to other occupational lung carcinogens. There was no evidence of a trend of increasing lung cancer risk with increasing duration of work as a firefighter (p = 0.58) and no significant heterogeneity in lung cancer risk among firefighters across the studies. None of the major histological subtypes of lung cancer was associated with work as a firefighter. Conclusions: We found no evidence of an excess lung cancer risk related to occupational exposure as a firefighter, when lifetime history of tobacco smoking and exposure to other occupational lung carcinogens was taken into account.